Transformasi Pendidikan Maksimalkan Potensi Belajar Dengan Media Pembelajaran Interaktif: Transformasi Pendidikan Maksimalkan Potensi Belajar Dengan Media Pembelajaran Interaktif - Atika Nur Hidayati; Ridwan Santoso (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2023)
Education in the digital era will continue to develop with the use of technology in the learning context becoming crucial to improving the quality of education. The main objective of this research is to understand the extent to which interactive learning media can contribute to strengthening students' conceptual understanding, stimulating their engagement, and encouraging the development of critical skills. The research method used is a qualitative approach. The research results show that educational transformation through interactive learning media significantly increases students' conceptual understanding and their involvement in the learning process. These results provide valuable insights into the effectiveness of education in a technological context, providing a foundation for further development in designing adaptive and innovative learning strategies in the modern era. The practical implications of these findings can help education administrators and educators maximize student learning potential through the application of relevant and interesting interactive learning media